Supramolecular Self-Assembly Of Π-Conjugated Organic Molecules: Toward Functional Materials for Organic Electronics - Dr. Kamalesh Kumar Patel (International Journal of Scientific Research in Chemistry, 2025)
The precise supramolecular self-assembly of π-conjugated organic molecules plays a critical role in the development of advanced materials for organic electronics, including organic field-effect transistors (OFETs), organic photovoltaics (OPVs), and organic light-emitting diodes (OLEDs). This paper reviews recent progress in the molecular design strategies that enable controlled self-assembly through non-covalent interactions such as π–π stacking, hydrogen bonding, and van der Waals forces. Special emphasis is placed on the impact of structural parameters—such as core planarity, side-chain engineering, amphiphilicity, and chirality—on electronic properties and solid-state morphology. Furthermore, we discuss the strong structure–property relationships governing charge transport, optical absorption/emission, and crystallinity. Representative π-conjugated systems, including perylene diimides (PDI), tetrathiafulvalenes (TTF), oligothiophenes, and phthalocyanines, are highlighted for their ability to form functionally relevant supramolecular architectures. This review aims to elucidate the design principles that guide the assembly of high-performance organic electronic materials and offers a perspective on future research directions for achieving scalable, stable, and efficient devices.